Preparation and characterization of biodegradable polyacrylic acid based hydrogel for agricultural application - Waham Ashaier Laftah, 1980-; Shahrir Hashim; Fakulti Kejuruteraan Kimia (2013)
Thesis (Ph.D (Kejuruteraan Polimer)) - Universiti Teknologi Malaysia, 2013